Perancangan Smart Village Platform Aplikasi Edukatif untuk Pengentasan Stunting serta Monitoring Kesehatan Ibu Hamil - Muhammad Ilham Alhari; Widia Febriyani; Wader Trisepa Jonson; Asti Amalia Nur Fajrillah (Jurnal Ilmiah Teknologi Informasi Asia, 2021)
The era of globalization is closely related to comprehensive technological developments in various fields. Digitalization in all sectors is undeniable, currently, digitalization is not only developing in cities, but several villages in Indonesia are starting to develop and build digital villages, known as smart villages. However, this has not developed optimally. Therefore, it is necessary to develop a smart village, especially in the health sector. In this study, a platform was designed that can be used to educate with the help of an application platform. The method used in this study was to conduct a survey with related parties and provide education on village programs to monitor the stunting of pregnant women and toddlers. In addition, the authors also held discussions to help the community. The hope of the educational platform related to stunting reduction is to support a national program to reduce stunting rates in Indonesia. Keywords: stunting; education platform; smart village